2022
DOI: 10.3390/educsci12070441
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for Introducing a Digital Aesthetic Dentistry Course in Undergraduate Program: Contents and Ways of Administration

Abstract: Background: Nowadays, digital dentistry is a fundamental skill that dentists need to acquire at this time. The digital workflow has gained acceptance and is widely used in most disciplines of dentistry. For this reason, it might be advisable to include this content in the undergraduate curriculum. The aim of this work was to create a course in digital aesthetic dentistry and evaluate its effectiveness. Methods: Dental students at the University of Verona (from third to sixth year) participated in a 2-h course … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Furthermore, the responses collected from the survey of third- and fourth-year dental students in our faculty indicate that the proposed method (the combined use of modular digital and 3D-printed dental models in university dental training) received good feedback from the participants in the survey. The findings of our survey were consistent with those of other studies found in the dental literature [ 65 , 66 , 67 , 68 , 69 , 70 ]. However, to our knowledge, few scientific studies have been dedicated to topics related to the influence of students’ age or academic year on their perception of the use of digital dentistry and technological advancement such as 3D-printing in dental education.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the responses collected from the survey of third- and fourth-year dental students in our faculty indicate that the proposed method (the combined use of modular digital and 3D-printed dental models in university dental training) received good feedback from the participants in the survey. The findings of our survey were consistent with those of other studies found in the dental literature [ 65 , 66 , 67 , 68 , 69 , 70 ]. However, to our knowledge, few scientific studies have been dedicated to topics related to the influence of students’ age or academic year on their perception of the use of digital dentistry and technological advancement such as 3D-printing in dental education.…”
Section: Discussionsupporting
confidence: 93%
“…Given this, it is also important that young clinicians, undergraduates and non-specialized dentists have the opportunities and possibilities to provide their patients with more than one aesthetic analysis and method to create digital and clinical mock-ups [15][16][17].…”
Section: Introductionmentioning
confidence: 99%